Psychoemotional state and needs of internally displaced persons: challenges of integration and directions of support - Bodnar , I.; Pavlova , Y.; Sofinskyi , R. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. The study of the psychoemotional state and needs of internally displaced persons (IDPs) is essential for developing effective support models that take into account the complexity of the issue and the multidimensionality of integration challenges in modern conditions. Purpose – to determine the peculiarities of the psychoemotional state and current needs of IDPs in Ukraine under wartime conditions, as well as to outline the main challenges of their integration and substantiate the directions of comprehensive support. Methods and organization of the research. The study was conducted based on an online survey of IDPs from various regions of Ukraine. The sample included 459 individuals (93,9% women) who had been in IDPstatus for at least three months. Results. The vast majority of respondents (93%) experience varying degrees of psychological tension, and more than a quarter show symptoms of emotional exhaustion or depressive state. The subjective feeling of safety among most IDPs remains low: only one-third feel safe, while more than 23% assess their situation as critically unsafe. The process of IDPs’integration into new communities is ongoing but incomplete: only 44,5% feel fully integrated, while almost half report partial integration. The presence of emotional ties to their previous place of residence and a high level of uncertainty about future plans (more than 30% undecided) call for a flexible state policy that combines support both for integration and for possible return. The key needs of IDPs remain housing and financial assistance (73.3% each), social support (49.6%), compensation for lost property (45.4%), employment, as well as medical and psychological care. Conclusion. To ensure a decent life for IDPs under wartime conditions, a comprehensive state and cross-sectoral strategy is needed, aimed at meeting the basic, psychological, and social needs of displaced persons, promoting the development of physical culture and sports as a means of supporting physical and mental health, as well as fostering long-term integration or facilitating return.